Improving Your Health Through Physical Exercise (Eurasian Journal of Humanities and Social Sciences, 2024)
For good health, not only factors such as diet, taking care of your movements and others are necessary, but also such a key factor as physical activity. This has been proven hundreds of times; when a person constantly engages in physical exercise, he easily achieves his goal. In addition, physical activity takes us to a new level of well-being in terms of education, science and other social spheres.